2014
DOI: 10.1007/s11684-014-0347-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of salivary matrix metalloproteinase-8 (MMP-8) in chronic periodontitis diagnosis

Abstract: Periodontitis is an inflammatory disease of the periodontium. Any imbalance between the matrix metalloproteinases (MMPs) secreted by neutrophils and tissue inhibitors initiates the destruction of collagen in gum tissue, leading to chronic periodontitis. This study aimed to correlate salivary levels of MMP-8 and periodontal parameters of chronic periodontitis to establish MMP-8 as a noninvasive marker for the early diagnosis of chronic periodontitis. The study involved 40 subjects visiting the periodontic OPD o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 27 publications
6
58
0
Order By: Relevance
“…In the present study, MMP‐8 levels in saliva are significantly higher in patients with periodontitis compared with healthy patients, which has been shown in several studies 6 , 31 , 32 . Periodontal clinical parameters are frequently found to be positively correlated with MMP‐8, and the observed correlation here with PD is in line with previous work 31 , 32 .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, MMP‐8 levels in saliva are significantly higher in patients with periodontitis compared with healthy patients, which has been shown in several studies 6 , 31 , 32 . Periodontal clinical parameters are frequently found to be positively correlated with MMP‐8, and the observed correlation here with PD is in line with previous work 31 , 32 .…”
Section: Discussionsupporting
confidence: 92%
“…After screening by reading the titles and abstracts, 95 studies were considered as potentially eligible and were read in full by the evaluators. At the end of the analyses, six articles published between 2008 and 2016 met all the inclusion criteria and were included in the present systematic review . The flowchart of article screening and selection process is displayed in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…When evaluating patients diagnosed with chronic periodontitis, Gupta et al observed higher MMP‐8 levels in SF of patients presenting chronic periodontal disease (348.26 ng/mL) when compared with subjects in the control group (190.91 ng/mL).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations